Odpowiedzi

Najlepsza Odpowiedź!
2009-12-27T16:29:18+01:00
2(x-1)-3(y+1)=0
3(x+y)-2(x-y)=9

2x-2-3y-3=0
3x+3y-2x+2y=9

2x-3y-5=0
x+5y=9

2x-3y=5
x+5y=9

2x-3y=5
x=9-5y

2(9-5y)-3y=5
x=9-5y

18-10y-3y=5
x=9-5y

18-13y=5
x=9-5y

-13y=5-18
x=9-5y

-13y=-13/:(-13)
x=9-5y

y=1
x=9-5y

y=1
x=9-5*1

y=1
x=9-5

y=1
x=4


2009-12-27T17:28:30+01:00
2(x-1)-3(y+1)=0
3(x+y)-2(x-y)=9

2x-2-3y-3=0
3x+3y-2x+2y=9

2x-3y=3+2
x+5y=9

2x-3y=5
x+5y=9

2x-3y=5
x=9-5y

2(9-5y)-3y=5
x=9-5y

18-10y-3y=5
x=9-5y

-13y=5-18
x=9-5y

-13y=-13 /: (-13)
x=9-5y

y=1
x=9-5*1

y=1
x=9-5

y=1
x=4


2009-12-27T17:42:26+01:00
2(x-1)-3(y+1)=0
3(x+y)-2(x-y)=9

2x-2-3y-3=0
3x+3y-2x+2y=9

2x-5-3y=0
x+5y=9

2x-5-3y=0
x=9-5y

2(9-5y)-5-3y=0
x=9-5y

18-10y-5-3y=0
x=9-5y

13-13y=0 |-13
x=9-5y

-13y=-13 |:(-1)
x=9-5y

y=1
x=9-5*1

y=1
x=4